Integrated phytochemical, biological and structure-based in silico evaluation of the thyroid modulatory potential of Kaji Nemu (Citrus limon (L.) Osbeck) from Assam - Yashmin, R; Ahmed, R; Jyoti, S Y; Kalita, J C (Plant Science Today, 2026)
Kaji Nemu (Citrus limon (L.) Osbeck), a unique citrus from Northeast India with extensive nutritional and therapeutic attributes, has been declared the state fruit of Assam and a geographical indication-certified commodity. Despite its known therapeutic activity, this study highlights the phytochemical potential of the methanolic peel extract of Kaji Nemu and its modulatory effects on thyroid-related pathways. The extraction yield was 10.39 %. Qualitative analysis detected tannins, alkaloids, phenols, saponins, flavonoids, terpenoids and carbohydrates. Quantitative analysis further showed that the extract contained 18.03 mg/g of total phenols, 2.25 mg/g of total flavonoids and 19.52 mg/g of total tannins. The antioxidant activity assay results showed an IC50 of 42.00 µg/mL in the DPPH assay, alongside strong FRAP and ABTS scavenging activities. The extract demonstrated cytotoxicity against HEK293 cells in the MTT assay, with an IC50 value of 177.7 µg/mL. Gas chromatography-mass spectrometry (GC-MS) analysis identified 93 phytochemicals in the extract and reported antioxidant, anti-inflammatory, anticancer and antithyroid activities. Virtual screening and molecular docking against the thyroid hormone receptor beta 1 (TRβ1) identified 3-tert-Butyl-4-hydroxyanisole, detected through GC-MS analysis, as the lead compound. It showed a strong binding affinity (-6.7 kcal/mol), which was higher than that of the reference antithyroid drug methimazole. HPLC analysis quantified vitamin E and C at 0.09 and 23.97 mg/mL, respectively, supporting its nutritional and functional value. ICP-MS mineral profiling identified sodium as the most abundant element (18.85 mg/L), followed by potassium, calcium and zinc. The study highlights the translational potential of underutilised citrus as safe, novel and effective candidates for thyroid-related treatment, meriting further mechanistic and in vivo studies.